Indian Perspectives in English Literary Scholarship: A Bibliometric Analysis - Katadah, Md. Abu; Alam, Abid Fakhre; Chaudhary, Mamta; Parmar, Pragya Singh; Islam, Md. Shariful; Saikh, Sakirul (Indian Journal of Information Sources and Services, 2025)
This study analyzes Indian contributions to English literature scholarship through a bibliometric approach, using the Web of Science Core Collection (WoSCC) database, 1,097 articles published from 2004 and 2023 were obtained, focusing on author co-authorships, research outputs, co-occurrence of author keywords, and affiliated countries. The researchers employed the R Studio and VoS Viewer tools for the present study to analysis data. The results show a steady increase in articles from 2013 to 2022. Affiliation institutions of the authors include University of Delhi, which leads with an attractive publication count is followed by University of Hyderabad which ranks second in terms of publications. In terms of author, Nayar Pk emerged as the author with the highest number of publications. In terms of document types, journal articles (764) have the number of highest publications, followed by Book reviews (176), poetry (55), and editorial materials (54). Based on the sources, Journal of Postcolonial Writing leads with 68 publications, followed by Journal of Commonwealth Literature with 55 publications, Explicator with 33 publications, and World Literature Today with 32 publications respectively. The study concludes by providing broader summary of English literary scholarship in Indian lens, using data from the WoS database. The findings indicate that in the last decades there is a significant growth, there is projections in the future it will continue to increase.